Assistance for MSMEs Samiler Crackers Wonosunyo with Innovations in Samiler Printing Tools - S. Wulandari, Indah Apriliana; Ravita Hanun, Nur; Amrulloh, Muhlasin; Sartono; Nuryulia Praswati, Aflit; D. Hermawan, Hardika; Maulidiyah, Indri (Warta LPM, 2025)
Samiler Crackers is a snack which very popular as a souvenirs from Wonosunyo Village, Pasuruan. The sweet and spicy flavor of taste become a customer reasons to reorder in the large quantities especially during Eid al Fitri Holiday. Often, the enterprises gets orders up to 1 tons on these day. One of the enterprises problem is still use conventional production equipment and seldom unable to fulfill the quantities order in the short periods of time. So they must to buy the crackers on the others supplier. Printing is stage which consuming much time and requires expertise of operators. So, this assistance is provide an innovation about Samiler Printing equipment, so that production process can be faster with uniform results. The printing process carried out manually for ± 3 minutes previously, can be eliminated to be 30-45 seconds with uniform of thickness and width.